PEMANFAATAN BUAH PEPAYA MENJADI KRIPIK PEPAYA GUNA MENINGKATKAN EKONOMI DAN KREATIVITAS WARGA DESA PANJER MELALUI SOSIALISASI DAN PELATIHAN PRODUKSI - Ridwanulloh, M. Ubaidillah; Safira, Intan; Hidayah, Farikha Nur; Amrullah, Muhammad Syafi'udin (Publika Citra Media, 2025)
Community service activities were carried out in Panjer Village, Plosoklaten District, Kediri Regency, targeting the village's PKK (Family Welfare Empowerment) women. The purpose of this activity was to enhance creativity, particularly among the PKK women, by introducing new innovations to process unripe papayas into food products, specifically papaya chips. This initiative aimed to increase the economic value of papayas processed into chips, create new business opportunities for the PKK women, and contribute to the local community's economy. The stages of the activity included observation and communication between the IAIN Kediri KKN community service team and the residents of Panjer Village. Preparations were then made, followed by the implementation of the activity, which involved delivering material on how to process unripe papayas into culinary products such as chips and conducting practical workshops on making the chips. An evaluation was conducted by the community service team to assess the participants' understanding of the chip-making process. The results of this community service activity showed that participants were able to produce their own papaya chips, which can serve as a family snack or as a potential business opportunity to generate additional income. Moreover, it demonstrated the effective use of locally available materials to create economically valuable products, whether on a group or individual basis.